Comparison of Humoral Immune Responses to Different Forms of Salmonella enterica Serovar Gallinarum Biovar Gallinarum - Kim, Nam-Hyung; Ha, Eun-Jin; Ko, Dae-Sung; Choi, Kang-Seuk; Kwon, Hyuk-Joon (Frontiers in Veterinary Science, 2020)
Fowl typhoid is caused by Salmonella enterica serovar Gallinarum biovar Gallinarum (SG), and live attenuated, rough vaccine strains have been used. Both humoral and cellular immune responses are involved in protection, but the humoral responses to different forms of SG antigens are unclear. In this study, we compared humoral responses to a killed oil-emulsion (OE) smooth vaccine (SG002) and its rough mutant vaccine (SR2-N6) strains using proteomics techniques. We identified two immunogenic outer membrane proteins (OmpA and OmpX), and the selected linear epitopes were successfully applied in peptide-ELISA. Our peptide- and total OMP-ELISAs were used to compare the temporal humoral responses to various SG antigens: OE SG002 and SR2-N6; live, killed [PBS-suspension (PS) and OE)] and mixed (live and PS) formulations of another rough vaccine strain (SG 9R); and orally challenge with a field strain. Serum antibodies to the linear epitopes of OmpA and OmpX lasted only for the first 2 weeks, but serum antibodies against OMPs increased over time. The rough strain (SR2-N6) and mixed SG 9R induced higher serum antibody titers than the smooth strain (SG002) and single SG 9R (OE, live and PS SG 9R), respectively. Infection with the field strain delayed the serum antibody response by ~2 weeks. Mucosal immunity was not induced by any formulation, except for infection with the field strain after SG 9R vaccination. Thus, our results may be useful to understand humoral immunity against various SG antigens and to improve vaccine programs and serological diagnosis in the field.